Enhancing tax education through multi-format gamified learning tools - Sulaiman, Norhayati; Khair Anwar, Irda Syahira; Mansor, Norul Akma; Abdul Wahab, Roslan (2025)
A gamified learning platform has been developed to make the study of taxation more engaging and accessible for undergraduate students. Featuring a range of interactive games, the platform includes a journey-based progression game where a character advances by answering tax questions correctly, as well as drag-and-drop tasks, fill-in-the-blank activities, and real-life scenarios enhanced with AI characters and voice interaction. These games cover various tax topics; each tailored with different levels of difficulty based on the topic's complexity and intended learning outcomes. By transforming technical tax content into interactive and relatable experiences, the platform helps students grasp complex concepts more effectively while encouraging active participation and critical thinking. The enjoyable and student-friendly design reduces learning anxiety and supports deeper understanding and practical application. With its potential for use not only in classrooms but also in professional training, this gamified approach offers a fresh and innovative solution for improving tax education through technology.